Laser engraving zipper preparation process and product thereof
Through the preparation of modified ABS materials, the problem of alloy plastic zippers being easily deformed and damaged during laser engraving is solved, achieving lower defective yield and higher product aesthetics and texture.
Patent Information
- Application Number
- CN202411882664.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-28
AI Technical Summary
Alloy plastic zippers are prone to damage such as cracks, burning, discoloration, deformation, etc. during laser engraving, resulting in high defective product rates, increasing production costs and affecting product quality and market competitiveness.
Zippered teeth are prepared by using modified ABS materials. By adding zinc oxide nanowhisker crystals, heavy calcium carbonate, polycarbonate, maleic anhydride graft polymer, toughener and hydroxypropyl cellulose to the ABS resin, the thermal stability, heat resistance and processing performance of the material are improved, and thermal expansion and deformation during the laser process are reduced.
It effectively reduces deformation and damage of zippered teeth during laser process, reduces the defective product rate, improves the aesthetics and texture of the product, and enhances market competitiveness.
Smart Images

Figure BDA0005198571740000061 
Figure BDA0005198571740000081 
Figure BDA0005198571740000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of zipper processing, and more specifically, to a laser engraved zipper preparation process and its product. Background Art
[0002] As an important component of clothing accessories, zippers need to provide more choices in color, material, shape, etc. to meet the unique needs of different consumers as consumers' personalized needs increase. Customized services will become an important development direction of the zipper industry. Companies can meet the special needs of consumers by providing personalized zipper designs. Among them, laser zippers use laser beams to precisely engrave or process the zipper surface to form unique patterns, textures or color effects to meet people's needs for the aesthetics of zippers.
[0003] Among them, laser zippers are mainly made of alloy plastics. The reason is that alloy plastic zippers usually give people a sense of high-end due to their sturdiness and durability. After laser treatment, its surface can form a unique pattern, texture or color effect, further enhancing its beauty and texture. However, in the actual production process, when performing laser engraving, the thermal expansion coefficient of alloy plastics is large, and the teeth of the zipper are relatively small. They are easily deformed after being heated during the laser process. The surface of alloy plastic zippers is prone to cracks, burning, discoloration and other damage phenomena, resulting in a large number of defective products. This not only increases production costs, but also seriously affects product quality and market competitiveness. Therefore, how to effectively prevent alloy plastic zippers from deforming during laser processing has become a technical problem that needs to be solved urgently. Summary of the invention
[0004] In order to solve the problem of cracks, burning, discoloration, deformation and other damages that easily occur on the surface of alloy plastic zippers when laser engraving is performed, the present application provides a laser engraved zipper preparation process and its product.
[0005] In a first aspect, the present application provides a laser engraved zipper preparation process, which adopts the following technical solution: A laser engraving zipper preparation process includes the following preparation steps: S1, passing the modified ABS material through a plastic teeth automatic injection molding machine mold to obtain zipper teeth, and then preparing the zipper teeth into a zipper; S3. Design the pattern and use laser equipment to laser engrave on the surface of the zipper teeth to obtain the finished product: The modified material is prepared by the following method: A: Dry the ABS resin and set aside; B: adding ABS resin, zinc oxide nano whiskers and heavy calcium carbonate into a high-speed mixer and stirring evenly to obtain a first mixed material; C: adding polycarbonate, maleic anhydride grafted polymer, toughening agent and hydroxypropyl cellulose to the first mixed material, and continuing to stir evenly to obtain a second mixed material; D: The second mixed material is extruded through a twin-screw extruder, and then cooled, pelletized and dried to obtain a modified ABS material.
[0006] In this application, zipper teeth are prepared by using a specific modified ABS material. The zipper teeth can be made into a relatively small volume, and the zipper teeth are guaranteed not to crack, burn, discolor, or deform during the laser process. The defective rate of zipper teeth is greatly reduced, reducing the waste of raw materials and production costs. After laser engraving, the modified ABS material can form a more unique, delicate, and lasting pattern, texture, or color effect, further improving the aesthetics and texture of the product. This makes the product more in line with the aesthetic needs of modern consumers and enhances market competitiveness.
[0007] By adding zinc oxide nanowhiskers to ABS resin, the thermal stability and heat resistance of the material can be improved. Zinc oxide nanowhiskers have excellent thermal conductivity and mechanical strength, which can effectively disperse the heat generated during the laser process and reduce the impact of thermal expansion on the zipper teeth, thereby avoiding deformation and cracks. Heavy calcium carbonate, as an inorganic filler, has high hardness and strength. Adding it to ABS resin can effectively improve the overall hardness and strength of the modified ABS material, so that the zipper teeth can better resist deformation and fracture when subjected to external forces. Polycarbonate and maleic anhydride grafted polymer, these two materials can improve the toughness and impact resistance of ABS resin, so that the zipper teeth can better withstand the impact and heat of the laser during laser engraving, and reduce the occurrence of cracks and burning. The addition of toughening agent and hydroxypropyl cellulose not only improves the processing performance of the material, but also makes the modified ABS material easier to mold during the injection molding process. The zipper teeth after molding are stable in size and high in precision, which helps to reduce the deformation of zipper teeth caused by improper material processing.
[0008] Through laser engraving, various clear patterns such as animals, landscapes, plants and figures can be engraved on the surface of zipper teeth.
[0009] Preferably, in step S2, the laser power of the laser is 5-50 W, the engraving speed is 50-500 mm / s, and the engraving depth is 0.001-2 mm.
[0010] By adopting the above technical solutions and optimizing the parameters of the laser, we can ensure the clarity and accuracy of the pattern, texture or color effect, and avoid damage such as burning, discoloration or excessive deformation of the material due to excessive energy, thus improving the durability and service life of the product. At the same time, while ensuring the quality of engraving, we can also improve production efficiency.
[0011] Preferably, the weight parts of the raw materials used to prepare the modified ABS material are as follows: ABS resin 40-50 parts 10-15 parts of zinc oxide nanowhiskers Heavy calcium carbonate 5-10 parts Polycarbonate 4-6 parts Maleic anhydride grafted polymer 1-2 parts Toughener 0.5-1 part Hydroxypropyl cellulose 4-8 parts.
[0012] By adopting the above technical solution, the weight of the raw materials used to prepare the modified ABS material is optimized, and the mechanical properties, heat resistance and processing properties of the modified ABS material are further improved. The modified ABS material exhibits good stability and heat resistance during the laser engraving process, is not prone to damage such as cracks, burning or discoloration, and is easy to form clear patterns and textures, thereby improving the aesthetics and texture of the laser zipper.
[0013] Preferably, the maleic anhydride grafted polymer is composed of ABS-g-MAH and PE-g-MAH in a weight ratio of 5:(1-2).
[0014] By adopting the above technical scheme, the type and amount of maleic anhydride grafted polymer are optimized, the compatibility of ABS resin with raw materials such as polycarbonate, heavy calcium carbonate and zinc oxide nanowhiskers is further improved, and the mechanical strength and heat resistance of the modified ABS resin are improved, so that the modified ABS material exhibits good stability and heat resistance during the laser engraving process, and is not prone to damage such as cracks, burning or discoloration.
[0015] Preferably, the heavy calcium carbonate is modified heavy calcium carbonate, which is prepared by the following method: 1) Dispersing heavy calcium carbonate in deionized water by stirring, adding aqueous ammonia under nitrogen protection, then heating to 58-72° C., stirring for 1-2 hours, filtering, washing the filter cake with anhydrous ethanol, drying, and then ultrasonically dispersing in acetone to obtain a suspension solution; 2) Dissolve stearic acid in acetone, heat to 57-81° C., add the suspension, raise the temperature to keep warm for 3-5 hours in a nitrogen atmosphere, and after the reaction is completed, slowly pour the reaction solution into an ethanol solution, filter, rinse with anhydrous ethanol, and dry to obtain modified heavy calcium carbonate.
[0016] Heavy calcium carbonate is easy to agglomerate in polymers to form larger particles, which is not conducive to the preparation of modified ABS materials. By modifying heavy calcium carbonate, its surface properties are changed, and its compatibility with polymer matrices such as ABS resin is improved, which helps to evenly disperse the modified heavy calcium carbonate in ABS resin and avoid the occurrence of agglomeration. It helps to form a more dense and uniform material structure, improve the strength and heat resistance of the composite modified material, and make the modified ABS material show good stability and heat resistance during laser engraving, and is not prone to damage such as cracks, burning or discoloration, and is easy to form clear patterns and textures.
[0017] During the preparation process, the modified heavy calcium carbonate is first treated with ammonia water and deionized water, and then ultrasonically dispersed with acetone to make its particle size more uniform and its dispersibility better, which helps to achieve more uniform dispersion in the ABS resin matrix and improve the compatibility with the resin, thereby enhancing the overall performance of the composite material. At the same time, the introduction of stearic acid makes the surface of the modified calcium carbonate particles covered with a layer of stearic acid molecules, which can prevent the agglomeration between the particles, enhance the compatibility between the heavy calcium carbonate and the polymer matrix, and is conducive to forming a stronger interface bonding force, thereby improving the overall mechanical properties of the material, helping the ABS material to resist thermal expansion and deformation at high temperatures, so that the modified ABS material can better maintain the stability of shape and size during the laser engraving process, and reduce the occurrence of problems such as cracks, burning and discoloration.
[0018] Preferably, the weight ratio of the heavy calcium carbonate, the ammonia water and the stearic acid is 10:(1-2):(3-5).
[0019] By adopting the above technical solution, the dosage of heavy calcium carbonate, ammonia water and stearic acid is optimized, so that the three can be fully reactive, the compatibility of heavy calcium carbonate is improved, and thus it is more evenly dispersed in the ABS resin, which is beneficial to improve the strength and heat resistance of the modified ABS resin.
[0020] Preferably, the average particle size of the heavy calcium carbonate is 1-5 μm.
[0021] By adopting the above technical solution, the average particle size of heavy calcium carbonate is optimized, which helps to form a good dispersion effect in the modified ABS material, reduce agglomeration and sedimentation, and thus improve the overall uniformity of the material. At the same time, it helps to improve the fluidity of the material, making the laser energy during laser engraving easier to be absorbed and converted by the material, thereby obtaining more delicate and clear patterns and textures.
[0022] Preferably, the polycarbonate is an aliphatic-aromatic polycarbonate.
[0023] Aliphatic-aromatic polycarbonate has a high melting point. When combined with ABS resin, it can effectively improve the heat resistance of the modified ABS material, allowing the zipper to better withstand high temperatures during laser engraving and reduce deformation and damage caused by thermal expansion. In addition, the fatty-aromatic polycarbonate molecular chain contains both aliphatic and aromatic structures, which makes it both flexible and mechanically strong, helping to improve the toughness of the modified ABS material and making the zipper teeth more durable when subjected to external forces.
[0024] Preferably, the toughening agent is a core-shell toughening agent with styrene-methyl methacrylate copolymer as the shell.
[0025] The toughening agent has good compatibility with polymer matrices such as ABS resin, so that the toughening agent can greatly improve the toughness of the zipper teeth without significantly reducing the stiffness of the ABS material, and enhance its impact and tear resistance. At the same time, the introduction of the core-shell structure toughening agent, due to its excellent thermal stability and dimensional stability, can significantly reduce the deformation of the zipper teeth after being heated, and the surface is prone to damage such as cracks, burning and discoloration.
[0026] In a second aspect, the present application provides a laser engraved zipper, which adopts the following technical solution: A laser engraved zipper, comprising a first chain belt and a second chain belt, wherein the first chain belt and the second chain belt are respectively provided with zipper teeth arranged at intervals on their edges, and at least one of the zipper teeth is provided with a pattern on its surface, and the zipper teeth are prepared by the laser engraved zipper preparation process described in the first aspect.
[0027] By adopting the above solution, the surface of the zipper teeth has clear patterns, unique aesthetics and texture, and good durability and stability, which makes the product more competitive in the market and can meet consumers' demand for high-quality and personalized products.
[0028] In summary, this application has the following beneficial effects: 1. Reduce deformation and damage: The modified ABS material effectively improves the thermal stability and dimensional stability of the material by adding inorganic fillers such as zinc oxide nanowhiskers and heavy calcium carbonate. These fillers can absorb and disperse the heat generated during the laser engraving process, reduce the thermal expansion coefficient of the material, and thus significantly reduce the deformation of the zipper teeth during the laser process. At the same time, the addition of toughening agents improves the toughness of the material, allowing the material to better resist cracks and burning when subjected to thermal stress, further reducing the production of defective products.
[0029] 2. Improve aesthetics and texture: After laser engraving, the modified ABS material can present a more delicate and clear pattern, texture or color effect. This is because the modified material has good processing performance and laser absorption performance, which enables the laser to accurately engrave the required pattern and texture. In addition, due to the improved thermal stability of the material, it is not easy to discolor and burn during the laser engraving process, thus maintaining the high-end and aesthetics of the product. DETAILED DESCRIPTION Example
[0030] ABS resin was purchased from Yuyao Deyi Plastic Chemical Co., Ltd. The brand is Chimei from Taiwan, China, and the grade is PA-758.
[0031] ABS-g-MAH was purchased from Dongguan Shengli New Materials Co., Ltd. with the model number XH6230IYNDCV.
[0032] PE-g-MAH was purchased from Dongguan Dayue Plastic Technology Co., Ltd. with the brand name DY-308.
[0033] Acrylate resin toughening agent was purchased from Foshan Ruishan Group Co., Ltd. with the brand name M-210.
[0034] Styrene-methyl methacrylate copolymer is produced by Kane Corporation in Japan. M-701.
[0035] Aromatic polycarbonate was purchased from Yutao Plastic Raw Materials Business Department in Zhangmutou, Dongguan City. The brand is Saudi Basic and the specification is PC DFL4034.
[0036] Aliphatic polycarbonate was purchased from Yutao Plastic Raw Materials Business Department in Zhangmutou, Dongguan City. The brand is THERMOCOMP and the specification is PC D351-701.
[0037] Aliphatic aromatic polycarbonate was purchased from Yutao Plastic Raw Materials Business Department in Zhangmutou, Dongguan City. The brand is SABIC and the specification is PC DL-003.
[0038] Example 1 A laser engraved zipper, comprising a first chain belt and a second chain belt, wherein the first chain belt and the second chain belt are respectively provided with zipper teeth arranged at intervals at their edges, and patterns are provided on the surfaces of the zipper teeth, and the zipper teeth are prepared by the following method: S1, passing the modified ABS material through a plastic teeth automatic injection molding machine mold to obtain zipper teeth, and then preparing the zipper teeth into a zipper; S3. Design the pattern and use laser equipment to laser engrave on the surface of the zipper teeth to obtain the finished product.
[0039] In step S2 , the laser power of the laser is 15 W, the engraving speed is 100 mm / s, and the engraving depth is 0.005 mm.
[0040] The modified material is prepared by the following method: A: Dry the ABS resin and set aside; B: Add 400 g of ABS resin, 100 g of zinc oxide nanowhiskers, and 50 g of heavy calcium carbonate (average particle size of 1-2 μm) into a high-speed mixer and stir evenly to obtain a first mixed material; C: Add 40 g of polycarbonate (aliphatic polycarbonate), 10 g of maleic anhydride grafted polymer (ABS-g-MAH), 5 g of toughening agent (acrylate resin toughening agent) and 40 g of hydroxypropyl cellulose to the first mixed material, continue to stir evenly, and obtain a second mixed material; D: The second mixed material is extruded through a twin-screw extruder, and then cooled, pelletized and dried to obtain a modified ABS material.
[0041] The difference between Example 2-3 and Example 1 is that the types of raw materials, amounts and experimental parameters for preparing the laser engraved zipper are different. The specific differences are shown in Table 1: Example 4 A laser engraved zipper. The difference between this embodiment and embodiment 1 is that the maleic anhydride grafted polymer is composed of ABS-g-MAH and PE-g-MAH in a weight ratio of 5:1.
[0042] Example 5 A laser engraved zipper. The difference between this embodiment and embodiment 1 is that the maleic anhydride grafted polymer is composed of ABS-g-MAH and PE-g-MAH in a weight ratio of 5:2.
[0043] Example 6 A laser engraved zipper. The difference between this embodiment and embodiment 1 is that the heavy calcium carbonate is modified heavy calcium carbonate, which is prepared by the following method: 1) 50 g of heavy calcium carbonate was stirred and dispersed in 100 g of deionized water, and 5 g of ammonia water was added under nitrogen protection, and then the temperature was raised to 58° C., stirred and reacted for 1 hour, filtered, and the filter cake was washed with anhydrous ethanol, dried, and ultrasonically dispersed in acetone to obtain a suspension solution; 2) 15 g of stearic acid was dissolved in 100 g of acetone, heated to 58° C., the suspension was added, and the temperature was raised to keep warm for reaction for 3 h in a nitrogen atmosphere. After the reaction was completed, the reaction solution was slowly poured into an ethanol solution, filtered, rinsed with anhydrous ethanol, and dried to obtain modified heavy calcium carbonate.
[0044] Example 7 A laser engraved zipper, the difference between this embodiment and embodiment 4 is that the heavy calcium carbonate is modified heavy calcium carbonate, which is prepared by the following method: 1) 50 g of heavy calcium carbonate was stirred and dispersed in 100 g of deionized water. Under nitrogen protection, 10 g of aqueous ammonia was added, and then the temperature was raised to 72° C., stirred and reacted for 2 h, filtered, and the filter cake was washed with anhydrous ethanol, dried, and then ultrasonically dispersed in acetone to obtain a suspension solution; 2) Dissolve 25 g of stearic acid in 100 g of acetone, heat to 81 ° C, add the suspension, and heat to a nitrogen atmosphere for 5 hours. After the reaction is completed, slowly pour the reaction solution into an ethanol solution, filter, rinse with anhydrous ethanol, and dry to obtain modified heavy calcium carbonate.
[0045] Example 8 A laser engraved zipper, the difference between this embodiment and embodiment 1 is that the toughening agent is a core-shell structure toughening agent with styrene-methyl methacrylate copolymer as the shell.
[0046] Example 9 A laser engraved zipper, the difference between this embodiment and embodiment 1 is that the polycarbonate is aliphatic-aromatic polycarbonate.
[0047] Example 10 A laser engraved zipper. The difference between this embodiment and embodiment 1 is that the amount of ABS resin used is 220g, and the amount of polycarbonate used is 220g.
[0048] Comparative Example Comparative Example 1 A laser engraved zipper. The difference between this comparative example and Example 1 is that calcium sulfate nanowhiskers are used instead of zinc oxide nanowhiskers.
[0049] Comparative Example 2 A laser engraved zipper. The difference between this comparative example and Example 1 is that microcrystalline cellulose is used instead of hydroxypropyl cellulose.
[0050] Comparative Example 3 A laser engraved zipper. The difference between this comparative example and Example 1 is that hard clay is used instead of heavy calcium carbonate.
[0051] Performance test and test method Appearance test: Use a magnifying glass with a magnification of 10 times to observe the laser engraved zippers prepared in Examples 1-10 and Comparative Examples 1-4, and randomly select 150 zipper teeth for observation. Statistically, those with burnt, discolored, unclear patterns, deformed zipper teeth, and cracks are all unqualified, and the number of unqualified ones is counted.
[0052] Then take a qualified laser engraved zipper for sliding performance test: install the zipper on the zipper sliding performance tester, set the sliding speed of the tester to 50 times per minute, the tension to 50N, and make the zipper slide on the smooth test surface at the set speed until a jam or abnormal sound occurs, and record the number of occurrences. If it exceeds 1500 times, the test is terminated. At the same time, take the zipper before laser engraving in Example 1 as blank comparative example 1, and purchase ABS-PC alloy metal zipper from Suqian Qingye E-commerce Co., Ltd. as blank comparative example 2, and conduct appearance test and sliding performance test.
[0053] Through the above test of the smoothness of the zipper during opening and closing and the convenience of operation, it was observed that laser engraving did not affect the sliding performance of the zipper. The experimental data is shown in Table 2: Table 2 Experimental data of Examples 1-10 and Comparative Examples 1-3 By comparing Example 1 with the blank comparative example 1, the blank comparative example 1 did not have any jamming or abnormal sound in the sliding performance test, while the abnormal sound occurred at 1123 times in Example 1; Comparing Example 1 with the blank comparative example 2, 49 defective products were found in the blank comparative example 2 after appearance inspection. In the sliding performance test, the number of jams or abnormal sounds in the blank comparative example 2 was significantly lower than that in Example 1.
[0054] By comparing Example 1 with Comparative Examples 1-3, defective products were found in all Comparative Examples 1-3 after appearance inspection, while there was no defective product in Example 1; the number of freezes or abnormal sounds in Comparative Examples 1-3 was significantly lower than that in Example 1; From the experimental data of Example 1 and Comparative Examples 1-3 and Blank Comparative Examples 1-2, it can be seen that the preparation process in the present application can ensure that the zipper teeth do not change color, burn, crack or deform during laser engraving, and the pattern is clear and the sliding performance is good.
[0055] Compared with Example 1 and Example 4-5, the sliding performance of Example 4-5 is significantly improved, indicating that by mixing ABS-g-MAH and PE-g-MAH in a specific weight ratio, the sliding performance of the laser zipper after laser engraving is improved.
[0056] By comparing Example 1 with Example 6, the sliding performance of Example 6 is significantly improved; By comparing Example 4 with Example 7, the sliding performance of Example 7 is significantly improved; It can be seen from the experimental data of Examples 1 and 6, 4 and 7 that modifying heavy calcium carbonate by the method of the present application is beneficial to improving the sliding performance of the laser zipper after laser engraving.
[0057] Comparing Example 1 with Example 8, the sliding performance of Example 6 is significantly improved, indicating that the core-shell structure toughening agent using styrene-methyl methacrylate copolymer as the shell can improve the sliding performance of the laser zipper after laser engraving.
[0058] Comparing Example 1 with Example 9, the sliding performance of Example 9 is significantly improved, indicating that the use of aliphatic-aromatic polycarbonate can improve the sliding performance of the laser zipper after laser engraving.
[0059] Comparing Example 1 with Example 10, the sliding performance of Example 10 is reduced, indicating that the sliding performance of the laser zipper after laser engraving can be improved by optimizing the amount of ABS resin and polycarbonate.
[0060] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but such modifications are protected by patent law as long as they are within the scope of the claims of the present application.
Claims
1. A laser engraved zipper preparation process, characterized in that: The method comprises the following preparation steps: S1, passing the modified ABS material through a plastic teeth automatic injection molding machine mold to obtain zipper teeth, and then preparing the zipper teeth into a zipper; S3. Design the pattern and use laser equipment to laser engrave on the surface of the zipper teeth to obtain the finished product: The modified material is prepared by the following method: A: Dry the ABS resin and set aside; B: adding ABS resin, zinc oxide nano whiskers and heavy calcium carbonate into a high-speed mixer and stirring evenly to obtain a first mixed material; C: adding polycarbonate, maleic anhydride grafted polymer, toughening agent and hydroxypropyl cellulose to the first mixed material, and continuing to stir evenly to obtain a second mixed material; D: The second mixed material is extruded through a twin-screw extruder, and then cooled, pelletized and dried to obtain a modified ABS material.
2. The laser engraving zipper preparation process according to claim 1, characterized in that: In step S2, the laser power of the laser is 5-50W, the engraving speed is 50-500mm / s, and the engraving depth is 0.001-2mm.
3. The laser engraving zipper preparation process according to claim 1, characterized in that: The maleic anhydride grafted polymer is composed of ABS-g-MAH and PE-g-MAH in a weight ratio of 5:(1-2).
4. The laser engraving zipper preparation process according to claim 1, characterized in that: The weight parts of the raw materials used to prepare the modified ABS material are as follows: ABS resin 40-50 parts 10-15 parts of zinc oxide nanowhiskers Heavy calcium carbonate 5-10 parts Polycarbonate 4-6 parts Maleic anhydride grafted polymer 1-2 parts Toughener 0.5-1 part Hydroxypropyl cellulose 4-8 parts.
5. The laser engraving zipper preparation process according to claim 1, characterized in that: The heavy calcium carbonate is modified heavy calcium carbonate, which is prepared by the following method: 1) Disperse heavy calcium carbonate in deionized water by stirring, add ammonia water under nitrogen protection, then heat to 58-72°C, stir and react for 1-2h, filter, wash the filter cake with anhydrous ethanol, dry and ultrasonically disperse in acetone to obtain a suspension solution; 2) Dissolve stearic acid in acetone, heat to 57-81°C, add the suspension, raise the temperature to keep warm for 3-5 hours in a nitrogen atmosphere, and after the reaction is completed, slowly pour the reaction solution into an ethanol solution, filter, rinse with anhydrous ethanol, and dry to obtain modified heavy calcium carbonate.
6. The laser engraving zipper preparation process according to claim 5, characterized in that: The weight ratio of the heavy calcium carbonate, the ammonia water and the stearic acid is 10:(1-2):(3-5).
7. The laser engraved zipper preparation process according to claim 5, characterized in that: The average particle size of the heavy calcium carbonate is 1-5 μm.
8. The laser engraving zipper preparation process according to claim 1, characterized in that: The polycarbonate is an aliphatic-aromatic polycarbonate.
9. The laser engraved zipper preparation process according to claim 1, characterized in that: The toughening agent is a core-shell structure toughening agent with styrene-methyl methacrylate copolymer as the shell.
10. A laser engraved zipper, characterized in that: The laser engraved zipper includes a first chain belt and a second chain belt, and the edges of the first chain belt and the second chain belt are respectively provided with zipper teeth arranged at intervals, and at least one of the zipper teeth is provided with a pattern on the surface. The zipper teeth are prepared by the laser engraved zipper preparation process described in any one of claims 1-9.